Present Remotely

Send the link below via email or IM

• Invited audience members will follow you as you navigate and present
• People invited to a presentation do not need a Prezi account
• This link expires 10 minutes after you close the presentation

Do you really want to delete this prezi?

Neither you, nor the coeditors you shared it with will be able to recover it again.

Simplifying and Solving Linear Equations

- with Jaylen Jefferson
by

Jaylen Jefferson

on 25 October 2012

Report abuse

Transcript of Simplifying and Solving Linear Equations

Jaylen Jefferson
8th Period Solving Equations Inverse Operation The Solving an equation that finds the variable at the same time. 2 * y = 12 (2 /2) * y = (12 / 2) y = 6 End The reciprocal is any number divided by 1. The reciprocal of 2 is 1/2 (half) Reciprocal Is sometimes called the Multiplicative Inverse *Any Number multiplied by its Reciprocal will come out to be 1* Like Terms Terms whose variables are both the same are called Like Terms. 12y + 7 + 2y = 68 *Like Terms* Distributive Property Distributive Property states that the product of a number and a sum is equal to the sum of the individual products of the addends and the number a(b + c) = a * b + a * c Solving Two-step Equations Step 1: Add 6 to both sides: 5x = 15
Step 2: Divide both sides by 5: x = 3 *A One Step Equation is an equatin that only needs to be solved with one step* *There may be other ways to do this but I couldn't find any other way* An equation that takes two steps to complete. 5x - 6 = 9 Solving
Multi-Step
Equations An equation that takes two or more steps to complete. 2(x + 1)-x = 5 Step 1: Distribute: Step 2: Work Out: 2x + 2 - x = 5 Step 3: Combine Like Terms:
2x + 2 - x = 5
x + 2 = 5 2 * x + 2 * 1 - x = 5 Solving Equations With Variables on Both Sides Its when you combine like terms until you get an answer like this:
3x = 9 Then you would just follow the steps that you would usually would to complete a One-Step Equation 3(x + 1x) - 1x = 27 / 3 x = 3 (3x / 3x) = (9 / 3x) 3x = 9 4x - 1x = 9 3x + 1x - 1x = 9 *Another way to combine like terms in an equation is to just do whatever operation that's behind the first like term*

ex: 8y - 4 + 3y = 49 Step 4: Do Final Steps:
x + (2 - 2) = (5 - 2)
x = 3 Thanks For Watchin'
Full transcript